I Dewa Putu Rai's Creative Process in Creating the Music Accompanying “Kumbang Atarung” Dance - Bisma, I Wayan Arya; Yudarta, I Gede (Journal of Aesthetics, Creativity and Art Management, 2024)
This study was conducted to explore creativity in the dance’s accompanyment musical work called "Kumbang Atarung" by a musical artist from Pengosekan, Ubud, Bali, Indonesia I Dewa Putu Rai so as to reveal his views and method of creating work. I Dewa Putu Rai is an artist who has courage, artistic intelligence, innovative spirit and high creative power. This study uses a qualitative descriptive approach, through observation and interview data collection techniques. One of the results of his creativity is the accompaniment to the Kumbang Atarung dance. The factors driving I Dewa Putu Rai's creativity can be explored through the theory of creativity drivers. As a dance accompaniment that combines elements of Kebyar and Legong, this work was created by exploring musical potentials as well as palegongan and kekebyaran playing techniques, which were then recomposed with other (new) opportunities.